An Evidence-based Study on Pharmacological Treatments of Non-Alcoholic Fatty Liver Disease Based on Traditional Persian Medicine - Hasheminasab, Fatemeh S.; Tajadini, Haleh; Setayesh, Mohammad (Current Traditional Medicine, 2020)
Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is one of the most prevalent liver diseases regarded as the primary cause of chronic liver disease, which may lead to hepatic failure. Despite the recent developments in the treatment of NAFLD, the necessity to find more efficient treatments has led to investigation on medicinal plants. Traditional Persian Medicine (TPM) is one of the oldest medical schools in the world. For treatment of NAFLD, different medicinal plants have been employed in TPM. Objective: Considering the public welcome for herbal medicines, the current evidence-based review study is conducted to investigate herbal remedies for NAFLD in TPM. Methods: Medicinal plants for treating NFALD were extracted according to three famous textbooks of Persian medicine. Then anti-obesity, hypolipidemic, hypoglycemic, antioxidative and hepatoprotective effects of these medicinal plants were investigated according to modern medicine. For this purpose, databases including Scopus, web of sciences, Pubmed, Google scholar and science direct were searched. Results: Investigations of Persian medicine textbooks resulted in deriving 53 herbs, which are useful for treating NAFLD. Searching through aforesaid databases showed that most of these plants can help to treat this disease in at least 2 ways. 25 herbs are effective in all 5 mentioned effects. Conclusion: It should be considered that in Persian medicine, first-line treatment is correction of life style, then if necessary, herbs are prescribed. However, this study showed that many herbs mentioned in Persian medicine for treatment of NAFLD might have a potential to aid patient with this disease.
Keywords: Traditional Persian medicine